A three‐component system incorporating Ppd‐D1, copy number variation at Ppd‐B1, and numerous small‐effect quantitative trait loci facilitates adaptation of heading time in winter wheat cultivars of worldwide origin. (15th March 2018) - Würschum, Tobias; Langer, Simon M.; Longin, C. Friedrich H.; Tucker, Matthew R.; Leiser, Willmar L.
Abstract: The broad adaptability of heading time has contributed to the global success of wheat in a diverse array of climatic conditions. Here, we investigated the genetic architecture underlying heading time in a large panel of 1, 110 winter wheat cultivars of worldwide origin. Genome‐wide association mapping, in combination with the analysis of major phenology loci, revealed a three‐component system that facilitates the adaptation of heading time in winter wheat. The photoperiod sensitivity locus Ppd‐D1 was found to account for almost half of the genotypic variance in this panel and can advance or delay heading by many days. In addition, copy number variation at Ppd‐B1 was the second most important source of variation in heading, explaining 8.3% of the genotypic variance. Results from association mapping and genomic prediction indicated that the remaining variation is attributed to numerous small‐effect quantitative trait loci that facilitate fine‐tuning of heading to the local climatic conditions. Collectively, our results underpin the importance of the two Ppd‐1 loci for the adaptation of heading time in winter wheat and illustrate how the three components have been exploited for wheat breeding globally. Abstract : Heading time in wheat, which is closely correlated with flowering time, is essential for adaptation to a large range of climatic conditions and thus for the worldwide success of wheat as a crop. Here, we employed a large panel of 1, 110 winter wheat cultivars of worldwide origin to revisit the genetic control of heading time. Our results reveal a three‐component system incorporating the photoperiod sensitivity locus Ppd‐D1, copy number variation at Ppd‐B1, and numerous small‐effect quantitative trait loci that facilitates fine‐tuning of heading time in wheat.